2016
DOI: 10.1097/j.pain.0000000000000337
|View full text |Cite
|
Sign up to set email alerts
|

Pain and motor processing in the human cerebellum

Abstract: Pain-related adaptations in movement require a network architecture that allows for integration across pain and motor circuits. Previous studies addressing this issue have focused on cortical areas such as the midcingulate cortex. Here, we focus on pain and motor processing in the human cerebellum. The goal of this study was to identify areas of activation in the cerebellum, which are common to pain and motor processing, and to determine whether the activation is limited to the superior and inferior cerebellar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 75 publications
6
54
0
2
Order By: Relevance
“…In our current findings, we found the increased activation mainly in the cerebel-lum posterior lobe, which might increase spinal noxious responses and decrease the latency of withdrawal from nociceptive stimulation [51]. Second, some researchers observed overlapping activation in bilateral cerebellum lobules VI and VIIb, when pain and motor processes were combined within the same experiment [53]. Thus, they proposed that the posterior cerebellum might be vital in pain-associated adaptations in movement [54].…”
Section: Altered Functional Connectivity Of Insulasupporting
confidence: 58%
“…In our current findings, we found the increased activation mainly in the cerebel-lum posterior lobe, which might increase spinal noxious responses and decrease the latency of withdrawal from nociceptive stimulation [51]. Second, some researchers observed overlapping activation in bilateral cerebellum lobules VI and VIIb, when pain and motor processes were combined within the same experiment [53]. Thus, they proposed that the posterior cerebellum might be vital in pain-associated adaptations in movement [54].…”
Section: Altered Functional Connectivity Of Insulasupporting
confidence: 58%
“…The right supplementary motor area (SMA) and left paracentral lobule are functionally connected to cerebellar regions during pain processing (Coombes and Misra, 2016). Left cerebellar hemispheres 4, 5, and 6 have been implicated in working memory and generalized aversive processing, while right vermis six functions in emotional processing (Schmahmann, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The cerebellum has been recently proposed to be associated with cognitive, sensorimotor, pain and affective information processing [2730], and to be involved in pathophysiological mechanism of migraine [31]. Moulton et al found that the cerebellar activation areas overlapped with both unpleasant picture viewing and heat pain in healthy subjects and suggested that the cerebellum may have specific areas associated with encoding of generalized aversive processing [32].…”
Section: Discussionmentioning
confidence: 99%